Fullmetal alchemist. 21 - Arakawa, Hiromu, 1973- (Viz Media ; Simon & Schuster [distributor], 2009)
"In an alchemical ritual gone wrong, Edward Elric lost his arm and his leg, and his brother Alphonse became nothing but a soul in a suit of armor. Equipped with mechanical 'auto-mail' limbs, Edward becomes a state alchemist, seeking the one thing that can restore his and his brother's bodies...the legendary Philosopher's Stone.A diabolical trap is set for President Bradley... If he is assassinated, a power vacuum will open that Mustang and his allies will be more than happy to fill. Then, while Ed is reunited from someone from his past, Al is separated from his body--his proxy armor body! Now who is filling his heavy metal shoes...? Plus, take a break from all the alchemical intrigue and homonculus backstabbing at the annual Resembool Spring Sheep Festival!"